You can't reason with them: Dismissing religious defectors as irrational. Issue 1 (8th July 2022) - Elnakouri, Abdo; McGregor, Ian
Abstract : Millions of people leave their religion every year. Such defection often results in religious persecution, ostracism, and heightened intergroup conflict. Yet little is known about the underlying perceptions of religious defectors and what intergroup processes predict hostility toward them. In two pre‐registered studies ( N = 512), we investigated how religious group members' thoughts and feelings about defectors may lead to ostracism and a lack of dialogue. In both studies, group members rated defectors as unlikeable and irrational. Further, the strength of group members' religious group identification (but not religious belief conviction) predicted dislike and unwillingness to relate wisely with defectors (Study 2). Implications for intergroup research and improving the experience of religious defectors are discussed.